Assesmen Pembelajaran di Raudhotul Athfal Baitur-Rahmah Sawitsari Sleman - Ahmad Ichsan Yafi Hutagalung; Lu'lu'ul Ilmi (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2019)
His research study to study learning assessment in RA Baitur-Rahmah Sawitsari Sleman. This research uses descriptive qualitative research methods. Data is collected through observation, interviews, and documentation, then the data is analyzed by reducing data, presenting data, and verifying data. The results of this study indicate the learning model in the RA Baitur-Rahmah class uses a group system with a security perspective that uses themes, classroom assessments are carried out with two teachers who have different assignments, reporting according to daily, weekly, monthly, and semester reports.